Study on the performance of Tungsten–Titanium alloy film as a diffusion barrier for iron in a flexible CIGS solar cell. (October 2015) - Gao, Zedong; Zhao, Ming; Zhuang, Daming; Fu, Engang; Li, Xiaolong; Ouyang, Liangqi; Guo, Li; Sun, Rujun; Kimura, Kenji; Nakajima, Kaoru
Highlights: A Tungsten–Titanium layer as a barrier for Fe in flexible CIGS solar cell. RBS was used to analyze the Fe distribution. The diffusion constant of the Fe diffusing in the W–Ti layer was measured. The activation energy of the Fe diffusing in the W–Ti layer was measured. A 291 nm-thick W–Ti layer can serve as the barrier for CIGS solar cells for 20 years. Abstract: A Tungsten–Titanium (W–Ti) diffusion barrier was prepared on an iron (Fe) substrate by means of magnetron sputtering with subsequent annealing at different temperatures. Rutherford Backscattering Spectrometry (RBS) was used to analyze the Fe distribution in the W–Ti layer. The diffusion constant D 0 = 3.4 × 10 −16 m 2 /s and the activation energy Q = 43 kJ/mol of the Fe diffusing in the W–Ti layer were subsequently calculated based on Fick's Second Law. The results demonstrated that a 291 nm-thick W–Ti barrier layer can be used to block Fe from diffusing into a CIGS solar cell for 20 years at a work temperature of 308 K (35 °C).